Effects o follicular fluid oxidative status on human mural granulosa cells, oocyte competency and ICSI parameters - Karabulut, Seda; Korkmaz, Oya; Kutlu, Pelin; Eren Gözel, Hilal; Keskin, İlknur (Elsevier, 2020)
Purpose: The aim of the present study was to understand the molecular and genetic alterations involved in follicular fluid oxidative process by investigating human mural granulosa cells and to find possible biomarkers for oocyte competency and ICSI outcome measures.Methods: A total of 166 patients were included in the study. Total antioxidant and oxidant levels of follicular fluids were measured on the day of oocyte pick-up and oxidative status were calculated. Expression profiles of three potential target proteins in cases of oxidative stress (Hsp70, Tgf-beta, Notch1), DNA status and chromatin integrity of mural granulosa cells were analyzed.Results: TAS levels were positively correlated with the Hsp70 and Tgf-beta expression patterns of mural granulosa cells. Mature oocyte rate and fertilization rates were affected negatively by the presence of oxidative stress and a significant positive correlation was found with the oxidative status and the fertilization rate, whereas no correlation with the remaining ICSI parameters in the overall group.Conclusions: Oxidative stress detected in follicular fluid adversely affects fertilization rates post-ICSI however no effect on the remaining parameters including embryo quality, pregnancy, and implantation rates. DNA damage, chromatin integrity were increased, whereas Hsp70 and Tgf-ss were decreased in mural granulosa cells in cases of oxidative stress which may indirectly reflect the oocyte competency and may be used as biomarkers for ICSI outcome measures.
Keywords: Oxidative Stress; Follicular Fluid; Intracytoplasmic Sperm Injection; DNA; Mural Granulosa Cells